PENINGKATAN KETERAMPILAN GURU MI DALAM MENGOPERASIKAN MEDIA ROKA'AT (RODA AKAR DAN PANGKAT) - Rohim, Abdur; Ningsih, Nur Alifatin; Fajrin, Amelia Nur (Universitas Mataram, 2024)
Many teachers have become accustomed to traditional learning methods that focus on textbooks and lectures. Not all teachers have the knowledge or skills to use instructional media, including the ROKA'AT media. Many of them may not have received sufficient training on the use of technology or new teaching methods. Therefore, the training attended by teachers from MI Bustanul Ulum Tumapel Gresik aims to improve their skills in operating the ROKA'AT media to support effective teaching methods. The training activities apply five stages: The observation stage, which involves direct observation and interviews regarding the environment of MI Bustanul Ulum Tumapel Gresik. The second stage is the socialization stage, providing information about the activities that will be carried out to address the problems. The third stage is the workshop, involving hands-on practice. The fourth stage is mentoring, and the fifth stage is the practice conducted by the participants to measure their understanding of the ROKA'AT media. Based on the final assessment obtained, the average ability of teachers to operate the media before the training was 25%, which increased to 32% after the training. This results in a gain score of 0.304, which falls into the medium category. In terms of competence, this activity can be generally considered successful, as participants were enthusiastic about the training, understood the material presented, and were able to skillfully apply the training material. The training received positive feedback and therefore should be further developed with well-organized follow-up activities.